Design of water bike for UMP Pekan lake - Chang, Chun Kit (2011)
The objective of this thesis is to design a water bike which can be manufacture in UMP and also can be used in UMP Pekan’s lake in the future.This water bike is easy to operate and easy to fabricate. This water bike will be design by using software. This water bike will purposely design for UMP Pekan’s Lake use. A prototype will be build and the structure of the water bike will be analyze. The main material for this project is mild steel hollow bar. The fabrication type will be more to cutting and welding to form the shape designed. Solidworks Simulation Xpress software is used to simulate the stress analysis on critical part of the water bike. Lastly, the objective of this project has been achieved where the water bike can be manufacture in UMP and used in UMP Pekan’s lake in the future